High-performance CsPbI3 perovskite solar cells without additives in air condition. (1st November 2021) - Saparbaev, Aziz; Zhang, Meili; Kuvondikov, Vakhobjon; Nurumbetova, Lobar; Raji, Ibrahim Oladayo; Tajibaev, Ilkhom; Zakhidov, Erkin; Bao, Xichang; Yang, Renqiang
Abstract: Perovskite Solar Cells (PSC) based on cesium lead triiodide (CsPbI3 ) perovskite have received great attention. However, the quality and thickness of perovskite active layers are still far from the level of perfection due to the limited solubility of the perovskite materials for PSC. Here, eco-friendly methylammonium acetate (MAAc) solution was used for stirring the CsPbI3 perovskite to transform from the yellow (orthorhombic) phase to the black (cubic) phase without additives. The high performance of CsPbI3 PSC has been achieved by annealing at low temperature with multiple coating, without any additives and anti-solution treatment, based on the combination of good film morphology, low-defect surface and longer carrier diffusion length reported for fabrication of good quality perovskite films in full air conditions. CsPbI3 perovskite film changes from yellow to black phase at low temperature on MAAc solution. Increasing thickness can improve the absorption of incident light and consequently improve the Power Conversion Efficiency (PCE) of 14.4% by significantly elevated device parameters of inverted planar PSC. The results reveal that the multiple coatings of CsPbI3 on MAAc solution without additives is a promising choice for good-stability and effective PSC. Highlights: High quality CsPbI3 perovskite film obtained in MAAc solution without additives. The pinholes and trap density of the films effectively eliminated by multiple drip coating. Power conversion efficiency of 14.4% was obtained in inverted planar PSC.